Media Informasi dalam Perwujudan Pemenuhan Perumahan dan Permukiman yang Berkelanjutan Bagi Masyarakat Berpenghasilan Rendah - B. Aldo Enzo Saputra; Asnawi Manaf (Jurusan Perencanaan Wilayah dan Kota, 2023)
The realization of sustainable housing and settlements is in line with the 33rd point of NUA (New Urban Agenda) regarding the provision of adequate housing for the entire citizen. NUA point 107 is the method regarding the development of regulations, tools, mechanisms that support access to affordable and sustainable housing for low-income group. The instruments that have been developed by stakeholders to provide housing that adequate are media, such as, mass media, the electronic media, and social media. The study was conducted on low-income group who live in Perumahan Curug Sewu Asri. Qualitative method was used in this study, with qualitative descriptive analysis and triangulation, by collecting data through in-depth interviews. The results showed that the respondent received information and spesifications of Curug Sewu Asri Housing through word of mouth. The informants did not feel that they had received a response and influenced by using media. In conclusion, the use of media in fulfilling sustainable housing and settlement in Curug Sewu Asri Housing has not been maximized. This can be one of considerations for local government to find out how far the impact of media to provide the fulfillment of sustainable housing in recent condition.